Type I Interferons and Natural Killer Cell Regulation in Cancer - Müller, Lena; Aigner, Petra; Stoiber, Dagmar (Frontiers in Immunology, 2017)
Type I interferons (IFNs) are known to mediate antitumor effects against several tumor types and have therefore been commonly used in clinical anticancer treatment. However, how IFN signaling exerts its beneficial effects is only partially understood. The clinically relevant activity of type I IFNs has been mainly attributed to their role in tumor immune surveillance. Different mechanisms have been postulated to explain how type I IFNs stimulate the immune system. On the one hand, they modulate innate immune cell subsets such as natural killer (NK) cells, on the other hand, type I IFNs also influence adaptive immune responses. Here, we review evidence for the impact of type I IFNs in immune surveillance against cancer and highlight the role of NK cells therein.